A study of two Philippine high schools a cross-cultural look at the education of girls and boys - Clark, Paul W. 1965- (Ann Arbor Michigan ProQuest Information and Learning Company, 2010)
While most schooling in the Philippines currently takes place in a coeducational setting, it seems apparent that, although they are attending the same high schools, boys and girls are not getting the same education. In many areas of the Philippines, boys' dropout rates are almost three times that of girls'. As more females graduate from college, women are rapidly replacing men in many fields. However, this does not mean that women are leaving their traditional responsibilities in the home. Quite the opposite, women are now finding themselves faced with double the work while men essentially find themselves without the training or skills to adapt to a changing society. This dissertation looks specifically at the schooling of two communities in the central Philippines. Looking at one school from a very rural village and another in a larger city, I examine the historical and sociological traditions of the Philippines and the island of Panay specifically. I investigate the reasons for girls' success while also looking at some reasons for boys' failure. I look closely at students' relationships with their schools, their teachers, their families, and with each other; I am trying to get a sense of how they perceive themselves and their world. This dissertation uses qualitative research methods including lengthy observation and interview of students, families and teachers. It draws from the traditions of phenomenology and grounded theory, and is constructed in an interpretive anthropological tradition in which the narration is in first person singular and, where possible, the present tense.--Abstract.
Thesis (Ph.D.)--McGill University, 2001.
Keywords: Education, Secondary -- Philippines; Women -- Education -- Philippines; Sex differences in education -- Philippines